Selling pattern and marketing system of Boro paddy in Purbadhala upazila of Netrakona district in Bangladesh (Progressive Agriculture, 2020)
Bangladesh is one of the major rice producing countries in the world; rice is the major crop of this highly populated agrarian country and this sector is by far the most important provider of rural employment. The study was designed to examinethe marketing system with selling pattern of paddy in selected areas of Netrakona district which is one of the important paddy producing areas of Bangladesh. Samples were purposively selected in order to meet the objectives. The total sample size was 45 respondents including 20 paddy farmers, 7 Faria, 5 Bepari, 5 Paiker and 8 Aratdar-cum- wholesaler. Primary data were collected through face to face interview with the farmers and intermediaries by the researcher himself during the month of November, 2013. The marketed surplus of all types of farms represents 72.07 percent of total quantity of paddy produced in this study area. Marketing functions performed by the farmers in the study area were selling of paddy, transportation, storage, grading, financing and market information. The marketing functions performed by the intermediaries were buying and selling of paddy, transportation, storage, processing, grading, financing, pricing, market information and risk bearing. Farmers and intermediaries transported their paddy to the market for sale by head/shoulder load, rickshaw, van, trolley, push cart, bi-cycle etc. In this study the researcher had found 10 marketing channels of paddy in the study area. In describing selling pattern of boro paddy, the study showed that the small farmers sold 64.17 percent of paddy and the medium and large farmers sold 70.37 and 75.00 percent of paddy, respectively. The small farmers recorded the highest number of sale (7) and the quantity offered per sale was the lowest i.e. 8.25 quintal. The number of sale for the large farms was the lowest (4) but the quantity sold per sale was the highest (53.57 quintal). The small, medium and large farmers sold 74, 39 and 25 percent of their total sale at the farm-gate and 26, 61 and 75 percent in the primary and secondary markets, respectively.Progressive Agriculture 31 (2): 104-118, 2020